Downregulation of PTEN expression in psoriatic lesions. (29th October 2013) - Li, Yadi; Man, Xiaohong; You, Liping; Xiang, Qing; Li, Hongyan; Xu, Bo; Chen, Zhihua; Zhang, Xiaoyan; Lian, Shi
Abstract Background Considerable studies showed that tumor suppressor phosphatase and tensin homolog (PTEN) deleted on chromosome 10 is a major tumor suppressor, which inhibits cell proliferation through inactivation of the PI3 kinase (PI3K)/Akt signal pathway. In many human tumors, there is loss of function or mutations in PTEN. In our previous study, it was found that Akt activity in psoriatic lesions increased compared with that in normal controls. However, the expression of PTEN and the correlation between PTEN and PI3K/Akt have not been investigated in patients with psoriasis. Materials and methods Skin tissue samples were obtained from 18 patients with psoriasis and 19 healthy controls. The expressions of PTEN were measured with quantitative real‐time polymerase chain reaction (RT‐PCR) assay, Western blotting, and immunohistochemistry. Results Quantitative RT‐PCR analysis demonstrated that the mRNA levels of PTEN in psoriatic lesions were decreased in comparison with that in normal skin. Western blotting and immunohistochemistry analysis of PTEN showed that PTEN protein was lowly expressed in psoriatic lesions compared with that in normal controls, which suggested that the reduction of PTEN mRNA expression leads to decreased PTEN protein levels. Conclusions The downregulation of PTEN expressions may play a role in the overactivation of the PI3K/Akt pathway in psoriatic lesions and correlate with the hyperproliferation of psoriatic keratinocytes.